Efficacy and safety of 8 weeks versus 12 weeks of treatment with grazoprevir (MK-5172) and elbasvir (MK-8742) with or without ribavirin in patients with hepatitis C virus genotype 1 mono-infection and HIV/hepatitis C virus co-infection (C-WORTHY): a randomised, open-label phase 2 trial. Issue 9973 (21st March 2015) - Sulkowski, Mark; Hezode, Christophe; Gerstoft, Jan; Vierling, John M; Mallolas, Josep; Pol, Stanislas; Kugelmas, Marcelo; Murillo, Abel; Weis, Nina; Nahass, Ronald; Shibolet, Oren; Serfaty, Lawrence; et al.
Summary: Background: Both hepatitis C virus (HCV) mono-infected and HIV/HCV co-infected patients are in need of safe, effective, all-oral HCV regimens. In a phase 2 study we aimed to assess the efficacy and safety of grazoprevir (MK-5172; HCV NS3/4A protease inhibitor) and two doses of elbasvir (MK-8742; HCV NS5A inhibitor) in patients with HCV mono-infection and HIV/HCV co-infection. Methods: The C-WORTHY study is a phase 2, multicentre, randomised controlled trial of grazoprevir plus elbasvir with or without ribavirin in patients with HCV; here, we report findings for previously untreated (genotype 1) patients without cirrhosis who were HCV mono-infected or HIV/HCV co-infected. Eligible patients were previously untreated adults aged 18 years or older with chronic HCV genoype 1 infection and HCV RNA at least 10 000 IU/mL in peripheral blood without evidence of cirrhosis, hepatocellular carcinoma, or decompensated liver disease. In part A of the study we randomly assigned HCV-mono-infected patients to receive 12 weeks of grazoprevir (100 mg) plus elbasvir (20 mg or 50 mg) with or without ribavirin (arms A1–3); in part B we assigned HCV-mono-infected patients to 8 or 12 weeks of grazoprevir (100 mg) plus elbasvir (50 mg) with or without ribavirin (arms B1–3) and HIV/HCV co-infected patients to 12 weeks of therapy with or without ribavirin. The primary endpoint was the proportion of patients achieving HCV RNA less than 25 IU/mL 12 weeks after end of treatment (SVR12). Randomisation was by presence or absence of ribavirin, 8 or 12 weeks of treatment, and dosage of elbasvir. Patients were stratified by gentoype 1a versus 1b. The patients, investigators, and study site personnel were masked to treatment group assignements but the funder was not. Analysis was by intention to treat. This trial is registered atClinicalTrials.gov, numberNCT01717326 . Findings: 218 patients with HCV mono-infection (n=159) and HIV/HCV co-infection (n=59) were enrolled. SVR12 for patients treated for 12 weeks with or without ribavirin ranged from 93–98% in mono-infected and 87–97% in co-infected patients. SVR12 rates in mono-infected and co-infected patients treated for 12 weeks without ribavirin were 98% (95% CI 88–100; 43/44) and 87% (95% CI 69–96; 26/30), respectively, and with ribavirin were 93% (95% CI 85–97; 79/85) and 97% (95% CI 82–100; 28/29), respectively. Among mono-infected patients with genotype 1a infection treated for 8 weeks, SVR12 was 80% (95% CI 61–92; 24/30). Five of six patients who discontinued early for reasons other than virological failure had HCV RNA less than 25 IU/mL at their last study visit. Virological failure among patients treated for 12 weeks occurred in seven patients (7/188, 4%) and was associated with emergence of resistance-associated variants to one or both drugs. The safety profile of grazoprevir plus elbasvir with or without ribavirin was similar in mono-infected and co-infected patients. No patient discontinued due to an adverse event or laboratory abnormality. The most common adverse events were fatigue (51 patients, 23%), headache (44, 20%), nausea (32, 15%), and diarrhoea (21, 10%). Interpretation: Once-daily grazoprevir plus elbasvir with or without ribavirin for 12 weeks in previously untreated HCV-mono-infected and HIV/HCV-co-infected patients without cirrhosis achieved SVR12 rates of 87–98%. These results support the ongoing phase 3 development of grazoprevir plus elbasvir. Funding: Merck & Co, Inc.